Fluorescence resonance energy transfer from tryptophan to folic acid in micellar media and deionised water - Mote, U. S.; Patil, S. R.; Bhosale, Siddharth H.; Han, Sung-Hwan; Kolekar, G. B. (Journal of Photochemistry and Photobiology B-Biology, 2011)
The fluorescence resonance energy transfer (FRET) from tryptophan (Trp) to folic acid (FA) in aqueous sodiumdodecyl sulphate, cetyltrimethyl ammonium bromide, and Brij-35 as well as deionised water was investigated using steady state and time resolved fluorescence techniques. The data obtained from steady state fluorescence spectral studies and time resolved measurement indicated that the FRET from Trp to FA occurred most effectively in aqueous sodium dodecyl sulphate micellar solutions. The distance between Trp and FA were evaluated. Binding constant, number of binding sites and thermodynamic parameters were determined for Trp-FA interactions in deionised water. The values of the thermodynamic parameters suggest that the hydrophobic forces and hydrogen bonding are the key interacting forces between Trp-FA interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quenching; Fluorescence resonance energy transfer (FRET); Folic acid; Foster theory; Stern-Volmer plot; Tryptophan

One-pot three-component synthesis and photophysical properties of highly fluorescent novel 4-alkyl-3-aryl-2,6-dicyanoanilines by using tris(hydroxymethyl)aminomethane as a catalyst - Kudale, A. S.; Kamble, S. B.; Gore, A. H.; Pisal, M. M.; Salokhe, A. T.; Kolekar, G. B.; Helavi, V. B. (Chemical Data Collections, 2019)
Novel 4-alkyl-3-aryl-2,6-dicyanoanilines were synthesized by a multi-component one-step reaction of aromatic aldehyde, malononitrile and aliphatic aldehyde using tris(hydroxymethyl)aminomethane (THAM) as a catalyst under microwave (MW) irradiation or conventional heating. The optimized reaction condition involved use of 2.5 equivalents of THAM under MW irradiation at 140 W using 20% MW power for 5 min or conventional heating at 80 °C for 8 h in dimethylformamide. The photophysical properties including λmax, quantum yield and Stokes’ shifts of newly synthesized molecules were studied. All compounds exhibited quantum yield in the range of 0.04–0.52 with respect to standard quinine sulphate having quantum yield 0.54. The Stokes’ shifts of all compounds were found in the range of 41–105 nm. The current strategy provides operationally simple protocol using THAM as a catalyst to synthesize 4-alkyl-3-aryl-2,6-dicyanoanilines with diverse structural features to make them available for exploration of their photophysical as well as biological applications.